The Effect of Intellectual Capital, Production Costs, and Operating Costs on Profitability - Leny Suzan; Chusnul Khotimah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2023)
A company's ability to maximize revenue while making the best use of its resources is referred to as profitability. It is stated that good profitability can improve a company's performance and draw in stakeholders. Technology limitations and a lack of human resource potential have led to a heavy reliance on imported pharmaceutical raw materials, which can result in high production costs and operating expenses that have an impact on a company's profitability. This demonstrates that the firm must efficiently manage its production costs, operational costs, and intellectual capital in to maximize the firm ’s potential and enhance profitability. Therefore, the goal of this study is to ascertain the impact of intellectual capital, production costs, and operating costs on profitability in the Pharmaceutical Sub-Sector listed on the Indonesia Stock Exchange (IDX) for the years 2017 through 2021. A corporation in the pharmaceutical industry that is listed on the IDX between 2017 and 2021 is the object of this research. In this study, 44 observation data were collected over 5 years from 9 corporations after issuing outlier data using the purposive sampling method. Panel data regression analysis with the EViews 12 program is the data analysis technique employed. The results of this study show that intellectual capital as measured by VAIC has a positive and significant effect on profitability. Meanwhile, production costs and operational costs partially do not affect profitability. Companies in the pharmaceutical sub-sector are expected to maintain profitability by utilizing their assets to obtain maximum profit. Additionally, risks that impact the loss in profitability in terms of the company's internal and external operations are cautioned against by advisors to businesses.